Influence of meteorological and environmental factors on pediatric urinary tract infections: insights from a 6-year retrospective study in Central China - Changzhen Li; Feng Tang; Lei Xi; Xiaomei Wang (Frontiers in Public Health, 2025)
ObjectivesTo investigate the association between meteorological factors and common uropathogens in children with urinary tract infections (UTIs) and assesses the potential influence of weather conditions on pediatric UTIs.Study designAnalyze the demographic and uropathogen characteristics from children with culture-proven UTIs and its correlation with meteorological factors.Methods2,411 data from infants and children with UTIs in a children’s hospital from 2016 to 2021 were retrospectively analyzed. A correlation analysis was conducted to investigate the relationship between the monthly detection number of uropathogens and meteorological factors.ResultsMultiple linear stepwise regression analyses showed a positive correlation between monthly average temperature, precipitation volume, sunshine hours, monthly total number of uropathogens, and the number of E. coli and E. faecalis. E. faecium was predominant in <12-month-old children, while E. coli was dominant in the 3–18-year age category. E. faecium showed a higher prevalence in girls, while E. faecalis was more prevalent in boys. E. coli exhibited resistance rates of >40% to second-or third-generation cephalosporins in multiple age groups. E. faecium showed high resistance rates to tetracyclines, fluoroquinolones, erythromycin, ampicillin, and penicillin, while K. pneumoniae displayed higher sensitivity to cephalosporin–sulbactam and amikacin, but higher resistance rates to cefazolin and ceftazidime.ConclusionThis study reveals the association between meteorological factors and uropathogens in children with UTIs, as well as the distribution, age-related characteristics, gender differences and antibiotic resistance profiles of pathogenic bacteria. These findings inform the development of targeted strategies for UTI prevention and treatment based on uropathogenic characteristics and meteorological conditions.